2012
DOI: 10.9753/icce.v33.waves.38
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Adv in Wave Flumes: Getting More Information About Waves

Abstract: This article discusses the advantages of measuring wave orbital velocities in coastal two-dimensional physical models in addition to free surface profiles. A brief presentation of linear theory for partial standing wave is made and early experimental works on this subject are reviewed. Since 2005, additional experiments have been conducted on wave flumes in Brazil (INPH, IPH/UFRGS) and in Portugal (LNEC), in order to characterize wave patterns in terms of velocity data obtained by ADVs. A few questions are pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…All experimental studies with bichromatic waves conducted in wave flumes (e.g., Okayasu et al 1996;Baldock et al 2000;Conde et al 2013Conde et al , 2014bde Bakker et al 2015;Alsina 2016, 2018) showed the presence of not only the first SubI but also the interference between higher harmonics. Previous works (Conde et al 2013(Conde et al , 2014bNeves et al 2012) have concluded that the interference became more easily identifiable in velocity data rather than in the surface elevation records. In wave basins, one expects that third-or higher-order interference may develop more easily, yet few studies have been conducted in order to quantify the effects of interference waves on the object being modeled or investigated.…”
Section: Shoaling and Refractionmentioning
confidence: 90%
See 1 more Smart Citation
“…All experimental studies with bichromatic waves conducted in wave flumes (e.g., Okayasu et al 1996;Baldock et al 2000;Conde et al 2013Conde et al , 2014bde Bakker et al 2015;Alsina 2016, 2018) showed the presence of not only the first SubI but also the interference between higher harmonics. Previous works (Conde et al 2013(Conde et al , 2014bNeves et al 2012) have concluded that the interference became more easily identifiable in velocity data rather than in the surface elevation records. In wave basins, one expects that third-or higher-order interference may develop more easily, yet few studies have been conducted in order to quantify the effects of interference waves on the object being modeled or investigated.…”
Section: Shoaling and Refractionmentioning
confidence: 90%
“…Eventual tilting of the instruments was corrected using the 19)-( 21). Each circle corresponds to a given instant of time t. cross-correlation matrix procedure proposed by Neves et al (2012). The SubI/IG wave was extracted applying the HHT, because of its capacity of analyzing nonstationary and nonlinear phenomena (Huang et al 1998).…”
Section: Experimental Methodologymentioning
confidence: 99%
“…Thus the size of the vector plot of the velocities for the reflected wave will also be directly proportional to the reflection coefficient. A summation of the incident and reflected velocity components yields Equation (5) as derived by Neves et al [16].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A plot of the resultant horizontal and vertical velocities u res and w res produces an elliptical shape as shown in Figure 2. This elliptical shape has a maximum and minimum radius (known hereafter as maxima and minima respectively) which can be calculated using Equations (6) and (7) ( [16]).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation